Consequences of excessive use of screens for children's health: an integrative literature review (Research, Society and Development, 2022)
The objective of the present study is to understand the effect of the use of screens in childhood and its consequences, since it is necessary to understand these repercussions in order to develop prevention strategies. As for the methodology, it is an integrative literature review that searched for articles in the Virtual Health Library (VHL) with the following descriptors: “screen time” AND “child development” and the filters: “full text”, “English” and “Portuguese” and in the time frame from 2016 to 2020. Of the 25 articles found, 7 were excluded due to escape from the theme, duplicity or absence of the full text available, with the final corpus consisting of 16 articles, which were categorized into two axes: (I) Direct influence of screen use on neuropsychomotor development and (II) Consequence of screen use on children's daily habits, with indirect influence on development. The use of screens inappropriately or with exaggeration can cause negative consequences for child development, such as: language impairment, cognitive deficit, emotional and behavioral difficulties. In addition, it may be associated with a higher risk of obesity, eating difficulties, sleep disorders, and psychological difficulties. Therefore, it is extremely important that the recommendations on the adequate time of screen use by children are followed, as well as, the use must be supervised to ensure that the content accessed is compatible with the age group.